PENGARUH PERAN GURU DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN DASAR-DASAR PEMASARAN KELAS X BISNIS DIGITAL SMKN 4 SURABAYA - Rafli Faiz Aqmal; Dwi Yuli Rakhmawati (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This study aims to examine the influence of teacher roles and school environment on students’ learning motivation in the Basic Marketing subject for Grade X Digital Business students at SMKN 4 Surabaya. Using a descriptive quantitative method, data were collected from 105 students through a saturated sampling technique. The findings reveal that both teacher roles and the school environment significantly influence students’ learning motivation, both partially and simultaneously. Teachers' roles as instructors, facilitators, and mentors, combined with a supportive and well-equipped school environment, enhance student enthusiasm and participation. Improving the quality of teaching and the school environment is essential for optimal vocational learning outcomes.